The effect of platelet lysate in culture of PDLSCs: an in vitro comparative study - Duaa A. Abuarqoub; Nazneen Aslam; Raghda B. Barham; Nidaa A. Ababneh; Diana A. Shahin; Abdallah A. Al-oweidi; Hanan D. Jafar; Mazin A. Al-Salihi; Abdalla S. Awidi (PeerJ, 2019)
Background Cellular therapy clinical applications require large-scale production of stem cells. Therefore, abundance, ease of isolation, and proliferative potential are the most important factors in choosing the appropriate source of cells for transplantation studies. Multipotent stem cells obtained from periodontal ligament (PDL) can be used in periodontal tissue regeneration. In this study, we aimed to evaluate and compare the characteristics of periodontal ligament stem cells (PDLSCs), extracted by either enzymatic digestion or explant methods, and expanded using two different serum types: fetal bovine serum (FBS) and xeno-free platelet lysate (PL). Methods Expanded PDLSCs were assessed for their proliferation capacity, surface markers expression, colony formation, differentiation potential and ability to self-renewal. Most importantly, PDLSCs were evaluated for their ability to produce osteoblasts in vitro. Results PDLSCs isolated by explant method and expanded in PL serve as a promising source of stem cells for osteoblasts regeneration. These cells showed higher proliferation capacity, they retained their stemness characteristics throughout the passages and they revealed an increase in the expression level of osteogenic markers, without showing any karyotypic abnormalities after cell expansion. Conclusions PDLSCs produced using explant extraction method and expanded in cell culture media supplemented with PL provide an excellent source of xeno-free cells for the generation of functional osteoblasts.